1993
DOI: 10.1177/000456329303000116
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Effect of Haematocrit on the Hemocue Blood Glucose Analyser

Abstract: SUMMARY. The HemoCue blood glucose analyser was investigated with particular respect to its susceptibility to influence by the haematocrit of the blood specimen. The red cells and plasma of fresh blood samples were separated and then recombined in proportions to give a range of haematocrit values and the resulting specimens assayed for glucose. The HemoCue exhibited no appreciable influence of haematocrit. The instrument was easy to use, stable and had good precision (CV 1'8%). However, results tended to be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 4 publications
1
16
1
3
Order By: Relevance
“…Although evaluation of the trueness of meters and strips was not the main objective of this study, it is interesting to note that only the HemoCue results did not show any deviation from the results of the conventional reference method, a finding that is in agreement with some studies (18 -20 ) but in contrast to others (21)(22)(23). For one of the instruments, the Accu-Chek Sensor, one lot showed a significantly larger deviation from the reference method than the other two lots.…”
Section: Discussionsupporting
confidence: 88%
“…Although evaluation of the trueness of meters and strips was not the main objective of this study, it is interesting to note that only the HemoCue results did not show any deviation from the results of the conventional reference method, a finding that is in agreement with some studies (18 -20 ) but in contrast to others (21)(22)(23). For one of the instruments, the Accu-Chek Sensor, one lot showed a significantly larger deviation from the reference method than the other two lots.…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings of higher blood glucose values using the HemoCue system in comparison with the YSI values have been reported in an adult population. 28 While this has been thought to be due to a more complete lysis of neonatal erythrocytes by the saponin,"8 we found this tendency even in comparison with the hexokinase method (in which proteins are denatured by perchloric acid), and the plasma method on Ektachem.…”
Section: Discussionmentioning
confidence: 56%
“…This has been further complicated by the fact that the device has been used a number of times for neonatal hypoglycemic samples, which are from a very specific patient group, different from adults in several ways. Although one study (46) showed no marked effect of hematocrit on glucose measurements presumably, although not mentioned specifically, in adult blood, it is possible that either hematocrit or other factors in neonatal blood have influenced the results (47). When discussing the data provided by studies on blood glucose measurement, we believe that the accuracy and variability of the reference method used should also be taken into account, as there is no generally accepted gold standard, except perhaps for isotope dilution mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%